Antimicrobial resistance of Escherichia coli, Salmonella sp and Vibrio sp in aquaculture-related surface water - Durra Natasha Izlynn Mohd Nizal (2020)
Antibiotics are reported to be used widely in aquaculture in order to prevent and treat fish diseases. Therefore aquaculture is considered to play a role in the epidemiology and emergence of antimicrobial resistance (AMR). This study determines the pattern of antimicrobial resistance among E. coli, Salmonella and Vibrio sp. from the surface water (freshwater and brackishwater) adjacent to aquaculture farms to highlight the impact of aquaculture activities on the development of resistance among the aforementioned bacteria. Twenty water samples were taken from two different sites upstream from IO aquaculture farms. Six farms were located in Negeri Sembilan and four farms were located in Selangor. A hundred (100) ml of the water samples was filtered using membrane filtration technique and cultured for E. coli, Vibrio sp., and Salmonella sp. E. coli and Vibrio sp. were isolated from surface water in Selangor (75% each) and Negeri Sembilan (83%, 50%). Only one sample was positive for Salmonella sp. E.coli shows highest level of resistant to erythromycin (76.9%). While, Vibrio sp. shows the highest resistance to ampicillin (100%). The percentage for multi-drug resistance was high for Vibrio sp. (76.5%) and moderate for E. coli (46.2%). When the level of antibiotic resistance and MDR of E. coli and Vibrio was compared to isolates from the aquaculture water from previous study, the resistance levels were all lower, however the difference was not significant. This study reveals that antibiotic resistance is a prevailing problem in the aquatic· environment and important pathogen exhibited almost complete resistance to a certain commonly used antibiotics. Therefore,· · judicious use of antibiotics need to be enforced among all aquatic fanning activities as a way to manage AMR.
Project paper (D.V.M) - Universiti Putra Malaysia, 2020.